Polishing pad and method of manufacturing semiconductor device using same
By using urethane-based prepolymers, foaming agents and curing agents in the polishing pads to adjust their compositions to improve sound absorption characteristics, the energy loss problem caused by thermal energy and vibration in the CMP process is solved, and the effect of improving the polishing rate and retaining performance is achieved.
Patent Information
- Application Number
- CN202411550259.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-11-06
- Filing Date
- 2024-11-01
- Publication Date
- 2025-05-06
AI Technical Summary
In the chemical mechanical planarization (CMP) process of semiconductor devices, the polishing pads have a reduced polishing rate due to energy losses caused by thermal energy and vibration, and there are challenges in optimizing the physical properties and processing properties of the polishing pads.
Using a polishing pad including urethane-based prepolymer, foaming agent and curing agent, by adjusting the type and content of the foaming agent and curing agent, the polishing pad has excellent sound absorption characteristics in the frequency range of 500Hz to 4,000Hz, and the maximum sound absorption coefficient reaches 0.1 or above.
By reducing energy losses caused by heat energy and vibration, the polishing rate is improved while maintaining the physical properties and processing properties of the polishing pads, and improving CMP performance and yield.
Smart Images

Figure CN119927785A_ABST
Abstract
Description
Technical Field
[0001] Embodiments relate to a polishing pad for a chemical mechanical planarization (CMP) process of a semiconductor device, and more particularly to a polishing pad having excellent sound absorption characteristics, by which energy loss caused by heat and vibration energy in a CMP polishing process can be minimized, and a method for preparing the same. Background Art
[0002] In the semiconductor manufacturing process, the chemical mechanical planarization (CMP) process refers to the steps of fixing a semiconductor substrate (such as a wafer) on a head and contacting the surface of a polishing pad mounted on a polishing disk, and moving the polishing disk and the head relative to each other to smooth out irregularities on the surface of the semiconductor substrate.
[0003] In such a CMP process, the polishing pad needs to have stable physical properties because it has a great influence on the surface processing quality of the semiconductor substrate. In particular, since the polishing rate of the CMP process may be sensitively changed by the components contained in the polishing pad and its physical properties, it is necessary to optimize the components contained in the polishing pad and its physical properties.
[0004] In addition, polishing is performed by friction energy in the CMP polishing process. In this case, energy loss may occur due to heat or vibration in the process, and this energy loss may lead to performance degradation, such as a reduction in polishing rate. In order to reduce energy loss, a technique of reducing rigidity by making a softer polishing pad has been used in the past. However, the reduced rigidity has a disadvantage that the leveling effect may be weakened. Therefore, there has been continuous research on a polishing pad that can minimize energy loss to increase the polishing rate without reducing the physical properties or processing performance of the polishing pad, and a method for preparing the same.
[0005] [Prior art literature]
[0006] (Patent Document 1) Korean Patent Application Publication No. 2016-0027075 Summary of the invention
[0007] Technical issues
[0008] Therefore, an embodiment is intended to provide a polishing pad having excellent sound absorption characteristics and an excellent polishing rate, so that energy loss caused by thermal energy and vibration energy can be minimized during a CMP polishing process without reducing the physical properties or processing performance of the polishing pad, and a method for manufacturing a semiconductor device using the polishing pad.
[0009] Solution to the problem
[0010] According to one embodiment, the polishing pad includes a polishing layer, wherein the polishing layer includes a urethane-based prepolymer, a foaming agent, and a curing agent, and has a maximum sound absorption coefficient of 0.1 or more measured at a frequency of 500 Hz to 4,000 Hz according to the following Equation 1.
[0011] [Equation 1] Sound absorption coefficient = (I i –I r ) / I i =(I a +I t ) / I i
[0012] In Equation 1, when the polishing pad is cut (diameter: 45 mm) to measure the sound pressure in an impedance tube according to KS F 2814-2, I i is the intensity of the incident sound, I r is the intensity of the reflected sound, I a is the intensity of absorbed sound, and I t is the intensity of transmitted sound.
[0013] According to another embodiment, a method of manufacturing a semiconductor device includes polishing a surface of a semiconductor substrate using the polishing pad.
[0014] Advantageous Effects of the Invention
[0015] According to one embodiment, the polishing pad can reduce noise and vibration within a specific frequency range. Specifically, the polishing pad has excellent sound absorption characteristics because its maximum sound absorption coefficient measured at a frequency of 500 Hz to 4000 Hz according to Equation 1 satisfies 0.1 or more. Therefore, since it can minimize energy loss caused by heat energy or vibration energy in the CMP polishing process, it has an excellent polishing rate.
[0016] More specifically, the polishing pad includes a urethane-based prepolymer, a foaming agent, and a curing agent, and the types and contents of the foaming agent and the curing agent are adjusted. Therefore, it is possible to reduce noise and vibration within a specific frequency range to minimize energy loss due to vibration energy; based on this, it is possible to maximize the efficiency of friction energy to increase the polishing rate.
[0017] Furthermore, since the polishing pad of this embodiment can improve the polishing rate by minimizing energy loss without degrading the physical properties and processing performance of the polishing pad, the CMP performance and yield can be improved when a semiconductor device is manufactured using the polishing pad. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The results of Test Example 1 are shown, in which the sound absorption coefficients of the polishing pads of Examples 1 to 3 and Comparative Examples 1 and 2 were measured according to the KS F 2814-2 standard.
[0019] Figure 2 A method for manufacturing a semiconductor device according to an embodiment is schematically illustrated.
[0020] [Attachment Component Number]
[0021] 100: polishing pad, 200: polishing disc, 300: dresser, 400: polishing slurry, 510: polishing head, 520: carrier, 600: semiconductor substrate (wafer) DETAILED DESCRIPTION
[0022] Next, the present invention will be described in detail and illustrated in conjunction with specific embodiments. The embodiments are not limited to the contents disclosed below. As long as the essence of the present invention is not changed, the embodiments can be modified into various forms.
[0023] In this specification, the terms related to each component are used to distinguish the differences between them and are not intended to limit the scope of the embodiments. In addition, in this specification, a singular expression is interpreted as including the plural unless otherwise specified in the context.
[0024] In the present specification, when a part is referred to as “comprising” a certain element, it is understood that other elements may be included, rather than excluding other elements, unless otherwise specifically stated.
[0025] In this specification, when a component is described as being located above / below another component or being connected or coupled to each other, it covers the case where these components are directly or indirectly formed, connected, or coupled through other components. In addition, it should be understood that the criteria of "above" and "below" of each component may vary depending on the direction of the object being observed.
[0026] Unless otherwise indicated, all numerical ranges related to physical properties, dimensions, and the like of components referred to herein are to be understood as being modified by the word "about".
[0027] In the present specification, in the numerical ranges limiting component size, physical properties, etc., when a numerical range limited to an upper limit and a numerical range limited to a lower limit are separately exemplified, it should be understood that the numerical range combining these upper and lower limits is also included in the exemplary range of the present invention.
[0028] Polishing pad
[0029] According to one embodiment, the polishing pad includes a polishing layer, wherein the polishing layer includes a urethane-based prepolymer, a foaming agent, and a curing agent, and has a maximum sound absorption coefficient of 0.1 or more measured at a frequency of 500 Hz to 4,000 Hz according to the following Equation 1.
[0030] [Equation 1] Sound absorption coefficient = (Ii –I r ) / I i =(I a +I t ) / I i
[0031] In Equation 1, when the polishing pad is cut (diameter: 45 mm) to measure the sound pressure in an impedance tube according to KS F 2814-2, I i is the intensity of the incident sound, I r is the intensity of the reflected sound, I a is the intensity of absorbed sound, and I t is the intensity of transmitted sound.
[0032] According to one embodiment, the polishing pad has a maximum sound absorption coefficient of 0.1 or more measured at a frequency of 500 Hz to 4,000 Hz according to the above Equation 1.
[0033] Specifically, according to KS F 2814-2, the polishing pad is cut, the sample is placed in an impedance tube, and a plane wave sound source is generated in the tube to measure the sound pressure. In this case, the operating frequency range is 500 Hz to 4,000 Hz. The sound absorption coefficient is calculated according to the above equation 1 using the measured sound pressure.
[0034] For example, the maximum sound absorption coefficient of the polishing pad measured at 500 Hz to 4,000 Hz, 750 Hz to 3,500 Hz, 1,000 Hz to 3,200 Hz, 1,500 Hz to 3,000 Hz, 1,500 Hz to 2,500 Hz, 1,600 Hz to 2,500 Hz, or 1,700 Hz to 2,300 Hz according to KS F 2814-2 may be 0.11 or more, 0.12 or more, 0.15 or more, 0.16 or more, 0.18 or more, or 0.2 or more.
[0035] In addition, the maximum sound absorption coefficient of the polishing pad measured at a frequency of 500 Hz to 1,500 Hz according to KS F 2814-2 may be 0.05 or more. For example, the maximum sound absorption coefficient of the polishing pad measured at 700 Hz to 1,500 Hz, 800 Hz to 1,500 Hz, 900 Hz to 1,500 Hz, or 1,000 Hz to 1,500 Hz according to KS F 2814-2 may be 0.06 or more, 0.07 or more, or 0.08 or more.
[0036] According to one embodiment, the maximum sound absorption coefficient measured at a frequency of 1,000 Hz to 1,500 Hz is 0.05 or more, and the maximum sound absorption coefficient measured at a frequency of 1,500 Hz to 3,000 Hz is 0.1 or more.
[0037] According to one embodiment, when the sound absorption coefficient is measured at a frequency of 500 Hz to 4,000 Hz according to KS F 2814-2, the polishing pad may have a sound absorption peak A of 0.05 or more at a frequency of 500 Hz to 1,500 Hz and a sound absorption peak B of 0.1 or more at a frequency of 1,600 Hz to 2,500 Hz.
[0038] Since the polishing pad of the embodiment has a maximum sound absorption coefficient that satisfies the above range, it is possible to reduce noise and vibration within a specific frequency range, thereby minimizing energy loss due to vibration energy; therefore, the efficiency of friction energy can be maximized, thereby achieving an excellent polishing rate.
[0039] According to one embodiment, when the polishing pad is used to polish the silicon oxide layer of a silicon wafer with a ceria slurry, the polishing rate (removal rate) can be up to to to or to
[0040]
Mathematical equation 1
[0041] In addition, when the polishing pad is used to polish the silicon oxide layer of a silicon wafer with a silicon dioxide slurry, according to the above mathematical equation 1, the polishing rate can reach to to or to
[0042] Polishing layer
[0043] According to one embodiment, the polishing pad includes a polishing layer. Specifically, the polishing pad includes a polishing layer containing a polyurethane resin.
[0044] The polishing layer includes a urethane-based prepolymer, a foaming agent, and a curing agent. Specifically, the polyurethane resin may be formed from a composition including a urethane-based prepolymer, a foaming agent, and a curing agent.
[0045] More specifically, the polishing layer includes a polyurethane-based resin, which is a reaction product of an urethane-based prepolymer, a blowing agent, and a curing agent, i.e., a cured product of a composition in which the components are mixed. Therefore, it includes a porous polyurethane-based resin. In addition, the polishing layer may include a plurality of pores formed by the blowing agent.
[0046] The polishing layer may have a thickness of, for example, 0.8 mm or more, 1 mm or more, 1.2 mm or more, or 1.5 mm or more, and 5 mm or less, 3 mm or less, 2.5 mm or less, or 2 mm or less. As a specific embodiment, the thickness of the polishing layer may be 0.8 mm to 5 mm or 1.5 mm to 3 mm.
[0047] The polishing layer may have, for example, 0.6 g / cm 3 Above, 0.7g / cm 3 Above, or 0.75g / cm 3 Above, and 0.9g / cm 3 Below, 0.85g / cm 3 Below, or 0.8g / cm 3 As a specific embodiment, the specific gravity of the polishing layer can be 0.6 g / cm 3 Up to 0.9g / cm 3 or 0.7g / cm 3 Up to 0.9g / cm 3 .
[0048] The polishing layer may have a hardness of, for example, 30 Shore D or more, 40 Shore D or more, or 50 Shore D or more, and 80 Shore D or less, 70 Shore D or less, 65 Shore D or less, or 60 Shore D or less. As a specific embodiment, the hardness of the polishing layer may be 30 Shore D to 80 Shore D or 50 Shore D to 65 Shore D.
[0049] The polishing layer may have, for example, a tensile strength of 5 N / mm2 or more, 10 N / mm2 or more, or 15 N / mm2 or more, and 30 N / mm2 or less, 25 N / mm2 or less, or 20 N / mm2 or less. As a specific embodiment, the tensile strength of the polishing layer may be 5 N / mm 2 Up to 30N / mm 2 or 15N / mm 2 Up to 25N / mm 2 .
[0050] The polishing layer may have an elongation of, for example, 50% or more, 70% or more, 90% or more, 106% or more, or 120% or more, and 300% or less, 250% or less, 200% or less, or 150% or less. As a specific embodiment, the elongation of the polishing layer may be 50% to 300% or 90% to 130%. The elongation may be an elongation at fracture.
[0051] As a specific example, the polishing layer may have a hardness of 50 Shore D to 65 Shore D, a strength of 15 N / mm2 Up to 25N / mm 2 Tensile strength, and elongation of 90% to 130%.
[0052] The pores exist in the polishing layer in a dispersed form.
[0053] The average diameter of the pores may be, for example, 10 μm to 60 μm, 10 μm to 50 μm, 20 μm to 50 μm, 20 μm to 40 μm, 10 μm to 30 μm, 20 μm to 25 μm, or 30 μm to 50 μm.
[0054] In addition, the total area of the pores may be 30% to 60%, 35% to 50%, or 35% to 43% based on the total area of the polishing layer. In addition, the total volume of the pores may be 30% to 70%, or 40% to 60% based on the total volume of the polishing layer.
[0055] The surface of the polishing layer may have grooves for mechanical polishing. The grooves may have a depth, width, and pitch designed according to the needs of mechanical polishing, without particular limitation.
[0056] According to one embodiment, the polishing pad includes a urethane-based prepolymer.
[0057] Prepolymers generally refer to polymers with relatively low molecular weights whose degree of polymerization is adjusted to a moderate level in order to facilitate the molding of products in the production process. Prepolymers can be molded by themselves or after reacting with another polymerizable compound. For example, prepolymers can be formed by reacting an isocyanate compound with a polyol.
[0058] The isocyanate compound used for preparing the urethane-based prepolymer may be one selected from the group consisting of aromatic diisocyanate, aliphatic diisocyanate, alicyclic diisocyanate, or a combination thereof.
[0059] The isocyanate compound may include, for example, one selected from the group consisting of 2,4-toluene diisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), 1,5-naphthyl diisocyanate, phenyl p-diisocyanate, toluene diisocyanate, 4,4′-diphenylmethyl diisocyanate, hexamethylene diisocyanate, dicyclohexylmethyl diisocyanate, isophorone diisocyanate, and combinations thereof.
[0060] The polyol is a compound including at least two hydroxyl groups (—OH) per molecule, and may include one selected from the group consisting of polyether polyol, polyester polyol, polycarbonate polyol, polycaprolactone polyol, and a combination thereof.
[0061] The polyol may include, for example, one selected from the group consisting of polytetramethylene ether glycol, polypropylene ether glycol, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 2-methyl-1,3-propylene glycol, 1,4-butylene glycol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, tripropylene glycol, and combinations thereof.
[0062] The polyol may have a weight average molecular weight (Mw) of 100 to 3,000 g / mol. For example, the weight average molecular weight of the polyol may be 100 to 3,000 g / mol, 100 to 2,000 g / mol, or 100 to 1,800 g / mol.
[0063] According to one embodiment, the polyol may include a low molecular weight polyol having a weight average molecular weight (Mw) of 100 to 300 g / mol and a high molecular weight polyol having a weight average molecular weight (Mw) of 300 to 1,800 g / mol.
[0064] In addition, the urethane-based prepolymer may have a weight average molecular weight (Mw) of 500 to 3,000 g / mol. For example, the weight average molecular weight of the urethane-based prepolymer may be 500 to 2,500 g / mol, 1,000 to 2,000 g / mol, or 1,000 to 1,500 g / mol.
[0065] According to one embodiment, the isocyanate compound used to prepare the urethane-based prepolymer may include an aromatic diisocyanate compound, and the aromatic diisocyanate compound, for example, may include 2,4-toluene diisocyanate (2,4-TDI) and 2,6-toluene diisocyanate (2,6-TDI). The polyol compound used to prepare the urethane-based prepolymer may include polytetramethylene ether glycol (PTMEG) and diethylene glycol (DEG).
[0066] According to one embodiment, the isocyanate compound used to prepare the urethane-based prepolymer may include an aromatic diisocyanate compound and an alicyclic diisocyanate compound. For example, the aromatic diisocyanate compound may include 2,4-toluene diisocyanate (2,4-TDI) and 2,6-toluene diisocyanate (2,6-TDI), and the alicyclic diisocyanate compound may include dicyclohexylmethyl diisocyanate (H12MDI). The polyol compound used to prepare the urethane-based prepolymer may include polytetramethylene ether glycol (PTMEG) and diethylene glycol (DEG).
[0067] The urethane-based prepolymer may have an isocyanate terminal group content (NCO%) of 5 wt % or more, 8 wt % or more, or 10 wt % or more, and 13 wt % or less, 12 wt % or less, or 11 wt % or less. As a specific embodiment, the urethane-based prepolymer may have an isocyanate terminal group content (NCO%) of 8 wt % to 11 wt % or 9 wt % to 10 wt %.
[0068] The isocyanate terminal group content (NCO%) of the urethane-based prepolymer can be designed by comprehensively adjusting the types and contents of the isocyanate compound and the polyol compound used to prepare the prepolymer, the process conditions such as temperature, pressure, and time in the preparation process, and the types and contents of the additives used in the preparation process.
[0069] If the isocyanate terminal group content (NCO%) of the urethane-based prepolymer satisfies the above range, in the subsequent reaction between the urethane-based prepolymer and the curing agent, the reaction rate, reaction time, and final cured structure can be adjusted from the perspective of the use and purpose of the final polishing pad to facilitate polishing performance.
[0070] According to one embodiment, the urethane-based prepolymer may have an isocyanate terminal group content (NCO %) of 8 wt % to 11 wt % or 9 wt % to 10 wt %.
[0071] If the NCO% of the urethane-based prepolymer is lower than the above range, electrical properties based on the chemically hardened structure in the polishing pad may be achieved, thereby failing to achieve the desired polishing performance in terms of polishing rate and flatness, and the polishing pad may have an excessively high cutting rate, which may also result in a shortened service life. On the other hand, if the NCO% exceeds the above range, defects such as scratches and vibration marks may appear on the surface of the semiconductor substrate.
[0072] The foaming agent is a component for forming a pore structure in the polishing layer, and may include one selected from the group consisting of a solid-phase foaming agent, a gas-phase foaming agent, a liquid-phase foaming agent, and a combination thereof.
[0073] According to one embodiment, the foaming agent may be a non-chlorine-based foaming agent that does not contain a chlorine component. In particular, it may not contain or minimize the use of chlorine-based foaming agent components commonly used in the preparation of polishing pads, such as vinylidene chloride (VDC). For example, based on the total weight of the foaming agent, the content of the non-chlorine-based foaming agent may be 50% by weight or more, 80% by weight or more, 90% by weight or more, 95% by weight or more, 97% by weight or more, 99% by weight or more, or 99.5% by weight or more, and 100% by weight or less or 99.5% by weight or less, as a specific embodiment, 80% by weight to 100% by weight, 90% by weight to 100% by weight, or 80% by weight to 99.5% by weight. In addition, based on the total weight of the blowing agent, the content of the chlorine-based blowing agent may be less than 20 weight %, less than 10 weight %, less than 5 weight %, less than 1 weight %, less than 0.5 weight %, or less than 0.3 weight %, and more than 0 weight %, more than 0.1 weight %, or more than 0.5 weight %, as specific embodiments, 0 weight % to 20 weight %, 0 weight % to 1 weight %, 0 weight % to 0.5 weight %, or 0.5 weight % to 20 weight %.
[0074] The foaming agent may include at least one selected from a solid phase foaming agent including particles having a hollow structure, a liquid phase foaming agent using a volatile liquid, and an inert gas.
[0075] As an example, the solid phase foaming agent may include hollow structure particles that expand and adjust their size by heating. The advantage of such a solid phase foaming agent is that it is used as a raw material in an expanded form, the size of the pores can be controlled to be uniform, and the particle size is uniform.
[0076] In addition, the solid phase foaming agent may also include expandable particles. Expandable particles are particles that have the property of expanding under heat or pressure. The size of the expandable particles in the final polishing layer can be determined by the heat or pressure applied in the method for preparing the polishing layer. The expandable particles are used as raw materials in the state of particles that have not been expanded in advance. The final size of the expandable particles is determined when they are expanded by the heat or pressure applied in the method for preparing the polishing layer.
[0077] The solid-phase foaming agent may have an average particle size of 5 μm to 100 μm, for example, 5 μm to 50 μm, 20 μm to 50 μm, 30 μm to 48 μm, or 35 μm to 45 μm. As described below, when the solid-phase foaming agent is a particle used in an expanded state in the raw material, the average particle size of the solid-phase foaming agent may refer to the average particle size of the expanded particles themselves. As described below, when the solid-phase foaming agent is a particle used in an unexpanded state in the raw material, it may refer to the average particle size of the particles after undergoing heat or pressure expansion in the preparation method.
[0078] The solid phase foaming agent in the form of expandable particles may include a resin shell; and an expansion inducing component wrapped in the shell. The expandable particles may be heated in the preparation method to evaporate the wrapped expansion inducing component to form a hollow structure.
[0079] For example, the housing may be composed of a thermoplastic resin. The thermoplastic resin may be at least one selected from the group consisting of an acrylonitrile-based copolymer, a methacrylonitrile-based copolymer, and an acrylic copolymer.
[0080] The thickness of the shell may be, for example, greater than 0.1 μm, greater than 0.5 μm, greater than 1 μm, greater than 2 μm, or greater than 3 μm, and less than 15 μm, less than 12 μm, or less than 10 μm; as a specific embodiment, 2 μm to 15 μm.
[0081] The expansion inducing component may include one selected from the group consisting of hydrocarbon compounds, tetraalkylsilane compounds, and combinations thereof. Specifically, the hydrocarbon compound may include one selected from the group consisting of ethane, ethylene, propane, propylene, n-butane, isobutane, n-butene, isobutylene, n-pentane, isopentane, neopentane, n-hexane, heptane, petroleum ether, and combinations thereof. The tetraalkylsilane compound may include one selected from the group consisting of tetramethylsilane, trimethylethylsilane, trimethylisopropylsilane, trimethyl-n-propylsilane, and combinations thereof.
[0082] The solid phase foaming agent may include particles treated with an inorganic component. In one embodiment, the solid phase foaming agent may be a foaming agent treated with silicon dioxide (SiO2) particles. Treating the solid phase foaming agent with an inorganic component may prevent aggregation between multiple particles. The solid phase foaming agent treated with an inorganic component may differ from a solid phase foaming agent that has not been treated with an inorganic component in chemical, electrical, and / or physical properties on the foaming agent surface.
[0083] As a specific example, the foaming agent for the polishing pad according to an embodiment includes a solid-phase foaming agent. The solid-phase foaming agent may include at least one selected from the group consisting of acrylonitrile-based copolymers, methyl methacrylate-based copolymers, methacrylonitrile-based copolymers, and acrylic acid-based copolymers.
[0084] The content of the solid-phase foaming agent may be greater than 0.1 parts by weight, greater than 0.5 parts by weight, or greater than 1 part by weight, and less than 5 parts by weight, less than 3 parts by weight, or less than 2 parts by weight, relative to 100 parts by weight of the urethane-based prepolymer. As a specific embodiment, the content of the solid-phase foaming agent may be 0.1 parts by weight to 5 parts by weight or 0.5 parts by weight to 2 parts by weight, relative to 100 parts by weight of the urethane-based prepolymer.
[0085] The type and content of the solid phase foaming agent can be designed according to the desired pore structure and physical properties of the polishing layer.
[0086] Meanwhile, the liquid-phase foaming agent can be introduced during the mixing and reaction of the prepolymer and the curing agent to form pores. The liquid-phase foaming agent does not participate in the reaction between the prepolymer and the curing agent. In addition, the liquid-phase foaming agent physically evaporates under the action of the heat generated during the mixing reaction of the prepolymer and the curing agent to form pores.
[0087] The volatile liquid-phase blowing agent may be in a liquid state at 25°C, and it does not react with an isocyanate group, an amide group, and an alcohol group. Specifically, the volatile liquid-phase blowing agent may be selected from the group consisting of cyclopentane, n-pentane, cyclohexane, n-butyrate, bis(perfluorobutyl)(trifluoromethyl)amine; and perfluoro compounds such as perfluorotributylamine, perfluoro-N-methylmorpholine, perfluorotripentylamine, and perfluorohexane. Commercially available perfluoro compound products include FC-40 (3M), FC-43 (3M), FC-70 (3M), FC-72 (3M), FC-770 (3M), FC-3283 (3M), and FC-3284 (3M).
[0088] In addition, the foaming agent may include a gas phase foaming agent. For example, the foaming agent may include a solid phase foaming agent and a gas phase foaming agent.
[0089] The gas phase blowing agent may include an inert gas. The gas phase blowing agent is introduced during the reaction of the urethane-based prepolymer and the curing agent to serve as a component for forming pores.
[0090] The type of inert gas is not particularly limited as long as it is a gas that does not participate in the reaction between the urethane-based prepolymer and the curing agent. For example, the inert gas may include one selected from the group consisting of nitrogen (N2), carbon dioxide (CO2), argon (Ar), helium (He), and a combination thereof.
[0091] The type and content of the gas phase foaming agent can be designed according to the desired pore structure and physical properties of the polishing layer.
[0092] Based on the total volume of the composition, the amount of inert gas introduced may be 10% to 30%. Specifically, based on the total volume of the composition, the amount of inert gas introduced may be 15% to 30%. Specifically, the gas-phase foaming agent may be introduced through a predetermined feed pipeline during the mixing of the urethane-based prepolymer, the solid-phase foaming agent, and the curing agent. For example, the feed rate of the gas-phase foaming agent is about 0.8L / min to about 2.0L / min, about 0.8L / min to about 1.8L / min, about 0.8L / min to about 1.7L / min, about 1.0L / min to about 2.0L / min, about 1.0L / min to about 1.8L / min, or about 1.0L / min to about 1.7L / min.
[0093] The curing agent is a compound that chemically reacts with the urethane-based prepolymer to form a final cured structure in the polishing layer. For example, it may include an amine compound or an alcohol compound. Specifically, the curing agent may include one selected from the group consisting of aromatic amines, aliphatic amines, aromatic alcohols, aliphatic alcohols, and combinations thereof.
[0094] According to one embodiment, the curing agent may include a non-chlorine-based curing agent that does not contain chlorine components. For example, based on the total weight of the curing agent, the content of the non-chlorine-based curing agent may be 50% by weight or more, 80% by weight or more, 90% by weight or more, 95% by weight or more, 97% by weight or more, 99% by weight or more, or 99.5% by weight or more, and 100% by weight or less or 99.5% by weight or less, as a specific embodiment, 80% by weight to 100% by weight, 90% by weight to 100% by weight, or 80% by weight to 99.5% by weight. In addition, based on the total weight of the curing agent, the content of the chlorine-based curing agent may be less than 20 weight %, less than 10 weight %, less than 5 weight %, less than 1 weight %, less than 0.5 weight %, or less than 0.3 weight %, and more than 0 weight %, more than 0.1 weight %, or more than 0.5 weight %, as specific embodiments, 0 weight % to 20 weight %, 0 weight % to 1 weight %, 0 weight % to 0.5 weight %, or 0.5 weight % to 20 weight %.
[0095] The curing agent may be at least one selected from a solid-phase curing agent and a liquid-phase curing agent.
[0096] The solid phase curing agent may contain an active hydrogen group. The solid phase curing agent may contain an amino group (-NH2) as an active hydrogen group.
[0097] In addition, the solid phase curing agent may be an ester compound containing two or more benzene rings. Specifically, the solid phase curing agent may include two or more ester groups in a molecule.
[0098] The solid phase curing agent may have, for example, a weight average molecular weight of 150 g / mol to 400 g / mol, 150 g / mol to 350 g / mol, 200 g / mol to 350 g / mol, 250 g / mol to 350 g / mol, or 300 g / mol to 350 g / mol. In addition, the solid phase curing agent may have a melting point (mp) of 100° C. to 150° C., 100° C. to 140° C., or 110° C. to 130° C.
[0099] In one embodiment, the solid phase curing agent includes at least one selected from the group consisting of bis(4-aminobenzoic acid)-1,3-propylidene ester (PDPAB), 4-aminobenzoic acid-4-(4-aminobenzoyl)oxyphenyl ester, 4-aminobenzoic acid-4-(4-aminobenzoyl)oxybutyl ester, 4-aminobenzoic acid-4-[4-(4-aminobenzoyl)oxy-3-methylbutoxy]butyl ester, and bis(methylaminobenzoic acid)methylene ester (MBNA).
[0100] The liquid phase curing agent may contain an active hydrogen group. The liquid phase curing agent may include at least one selected from the group consisting of an amino group (-NH2), a hydroxyl group (-OH), a carboxylic acid group (-COOH), an epoxy group, and a combination thereof as an active hydrogen group. Specifically, it may contain an amino group (-NH2).
[0101] Furthermore, the liquid phase curing agent may contain sulfur in its molecule. Specifically, it may contain two or more sulfur elements in its molecule.
[0102] The liquid curing agent may have a weight average molecular weight of 50 g / mol to 300 g / mol, for example 100 g / mol to 250 g / mol, for example 150 g / mol to 250 g / mol, for example 200 g / mol to 250 g / mol.
[0103] In addition, the liquid phase curing agent may be in a liquid state at room temperature. Alternatively, the liquid phase curing agent may have a boiling point (bp) of 160°C to 240°C, specifically 170°C to 240°C, and more specifically 170°C to 220°C.
[0104] Examples of the liquid-phase curing agent include at least one selected from the group consisting of 3,5-dimethylthio-2,6-diaminotoluene (DMTDA), 2,6-bis(methylthio)-4-methyl-1,3-phenylenediamine, and N,N′-bis(sec-butylamino)diphenylmethane.
[0105] In addition, the curing agent may also include other curing agents in addition to the liquid phase curing agent and the solid phase curing agent. The additional curing agent may be, for example, at least one of an amine compound and an alcohol compound. Specifically, the additional curing agent may include at least one compound selected from the group consisting of aromatic amines, aliphatic amines, aromatic alcohols, and aliphatic alcohols.
[0106] For example, the additional curing agent may be at least one selected from the group consisting of diaminodiphenylmethane, diaminodiphenyl sulfone, meta-xylylenediamine, isophoronediamine, ethylenediamine, diethylenetriamine, triethylenetetramine, polypropylenediamine, polypropylenetriamine, ethylene glycol, diethylene glycol, dipropylene glycol, butanediol, hexanediol, glycerol, and trimethylolpropane.
[0107] As a specific example, the curing agent may include at least one selected from the group consisting of 4,4′-methylenebis(2-chloroaniline) (MOCA), diethyltoluenediamine (DETDA), 3,5-dimethylthio-2,6-diaminotoluene (DMTDA), 1,3-propylidene bis(4-aminobenzoate) (PDPAB), N,N′-bis(sec-butylamino)diphenylmethane, 2,6-bis(methylthio)-4-methyl-1,3-phenylenediamine, 4-aminobenzoic acid-4-(4-aminobenzoyl)oxyphenyl ester, 4-aminobenzoic acid-4-(4-aminobenzoyl)oxybutyl ester, 4-aminobenzoic acid-4-[4-(4-aminobenzoyl)oxy-3-methylbutyloxy]butyl ester, and bis(methylaminobenzoic acid) methylene ester (MBNA).
[0108] The content of the curing agent may be 5 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, or 20 parts by weight or more, and 50 parts by weight or less, 45 parts by weight or less, 40 parts by weight or less, 35 parts by weight or less, 30 parts by weight or less, or 25 parts by weight or less, relative to 100 parts by weight of the urethane-based prepolymer. The content of the curing agent may be 10 to 40 parts by weight, more specifically 15 to 35 parts by weight or 15 to 25 parts by weight, relative to 100 parts by weight of the urethane-based prepolymer.
[0109] In addition, the equivalent ratio of the urethane-based prepolymer to the curing agent may be 1:0.5 to 2. For example, the equivalent ratio of the urethane-based prepolymer to the curing agent may be 1:0.5 to 1.8, 1:0.5 to 1.5, 1:0.5 to 1.0, 1:0.6 to 1.2, 1:0.8 to 1.2, or 1:0.8 to 1.0.
[0110] When the equivalent ratio of the urethane-based prepolymer and the curing agent satisfies the above range, noise and vibration within a specific frequency range can be reduced, thereby minimizing energy loss due to vibration energy; therefore, the efficiency of friction energy can be maximized to increase the polishing rate.
[0111] The composition for preparing the polishing layer may also include other additives such as surfactants and reaction rate controllers. Names such as "surfactants" and "reaction rate controllers" are arbitrary names based on the main effects of these substances. Each substance does not necessarily perform only the function defined by the name.
[0112] The surfactant is not particularly limited as long as it can prevent the pores from merging and overlapping each other. For example, the surfactant may include a silicon-based surfactant.
[0113] The surfactant can be used in an amount of 0.2 to 2 parts by weight relative to 100 parts by weight of the urethane-based prepolymer. Specifically, the surfactant can be used in an amount of 0.2 to 1.9 parts by weight, 0.2 to 1.8 parts by weight, 0.2 to 1.7 parts by weight, 0.2 to 1.6 parts by weight, 0.2 to 1.5 parts by weight, or 0.5 to 1.5 parts by weight relative to 100 parts by weight of the urethane-based prepolymer. If the amount of the surfactant is within the above range, the pores generated by the gas-phase foaming agent can be stably formed and maintained in the mold.
[0114] The function of the reaction rate controller is to promote or inhibit the reaction. A reaction accelerator, a reaction inhibitor, or both can be used as needed. The reaction rate controller may include a reaction accelerator. For example, the reaction rate controller may be at least one reaction accelerator selected from the group consisting of a triamine compound and an organometallic compound.
[0115] Specifically, the reaction rate controller may include a compound selected from the group consisting of triethylenediamine, dimethylethanolamine, tetramethylbutylenediamine, 2-methyltriethylenediamine, dimethylcyclohexylamine, triethylamine, triisopropanolamine, 1,4-diazabicyclo[2.2.2]octane, bis(2-methylaminoethyl)ether, trimethylaminoethylethanolamine, N,N,N,N,N″-pentamethyldiethylenetriamine, dimethylaminoethylamine, dimethylaminopropylamine, benzyldimethylamine, N-ethylmorpholine, At least one of the group consisting of N,N-dimethylaminoethylmorpholine, N,N-dimethylcyclohexylamine, 2-methyl-2-azanorbornane, dibutyltin dilaurate, stannous isooctanoate, dibutyltin diacetate, dioctyltin diacetate, dibutyltin maleate, di(2-ethylhexanoate)dibutyltin, and dibutyltin dithiol. Specifically, the reaction rate controller may include at least one selected from the group consisting of benzyldimethylamine, N,N-dimethylcyclohexylamine, and triethylamine.
[0116] The reaction rate controller may be used in an amount of 0.05 to 2 parts by weight relative to 100 parts by weight of the urethane-based prepolymer. Specifically, the reaction rate controller may be used in an amount of 0.05 to 1.8 parts by weight, 0.05 to 1.7 parts by weight, 0.05 to 1.6 parts by weight, 0.1 to 1.5 parts by weight, 0.1 to 0.3 parts by weight, 0.2 to 1.8 parts by weight, 0.2 to 1.7 parts by weight, 0.2 to 1.6 parts by weight, 0.2 to 1.5 parts by weight, or 0.5 to 1 parts by weight relative to 100 parts by weight of the urethane-based prepolymer. If the amount of the reaction rate controller is within the above range, the curing reaction rate of the prepolymer composition can be appropriately controlled, thereby forming a polishing layer having a desired pore size and hardness.
[0117] Support layer
[0118] According to an embodiment, the polishing pad may include a support layer.
[0119] The support layer constitutes a base pad and is used to support the polishing layer and absorb and disperse the impact applied to the polishing layer. Therefore, in the polishing process using the polishing pad, it can minimize damage and defects to the polishing object.
[0120] The support layer may be composed of non-woven fabric or suede, but is not limited thereto.
[0121] In one embodiment, the support layer may be a resin-impregnated nonwoven fabric. The nonwoven fabric may be a fiber nonwoven fabric including at least one selected from the group consisting of polyester fiber, polyamide fiber, polypropylene fiber, and polyethylene fiber.
[0122] The resin impregnated in the non-woven fabric may include at least one selected from the group consisting of polyurethane resin, polybutadiene resin, styrene-butadiene copolymer resin, styrene-butadiene-styrene copolymer resin, acrylonitrile-butadiene copolymer resin, styrene-ethylene-butadiene-styrene copolymer resin, silicone rubber resin, polyester-based elastomer resin, and polyamide-based elastomer resin.
[0123] The support layer may have a thickness of, for example, 0.3 mm or more or 0.5 mm or more and 3 mm or less, 2 mm or less, or 1 mm or less. As a specific embodiment, the support layer may have a thickness of 0.3 mm to 3 mm or 0.5 mm to 1 mm.
[0124] The support layer may have a hardness of, for example, 50 Asker C or more, 60 Asker C or more, or 70 Asker C or more, and 100 Asker C or less, 90 Asker C or less, or 80 Asker C or less. As a specific embodiment, the hardness of the support layer may be 50 Asker C to 100 Asker C or 60 Asker C to 90 Asker C.
[0125] In addition, an adhesive layer may be interposed between the polishing layer (top pad) and the support layer (bottom pad).
[0126] The adhesive layer may include a hot melt adhesive. The hot melt adhesive may include at least one selected from the group consisting of polyurethane resin, polyester resin, ethylene-vinyl acetate resin, polyamide resin, and polyolefin resin. Specifically, the hot melt adhesive may be at least one selected from the group consisting of polyurethane resin and polyester resin.
[0127] In addition, a double-sided tape may be laminated under the support layer. When it is applied to a CMP device, after removing the release paper of the double-sided tape, it can be attached to a polishing pad for use.
[0128] Method for preparing polishing pad
[0129] According to one embodiment, a method for preparing a polishing pad includes preparing a polishing pad composition including a urethane-based prepolymer, a foaming agent, and a curing agent; injecting the polishing pad composition into a mold and curing to prepare a polishing layer; and laminating the polishing layer and a support layer.
[0130] The specific types and contents of the urethane-based prepolymer, curing agent, and blowing agent are as described above.
[0131] As a specific embodiment, the foaming agent includes a solid-phase foaming agent, the solid-phase foaming agent includes at least one selected from the group consisting of acrylonitrile-based copolymers, methyl methacrylate-based copolymers, methacrylonitrile-based copolymers, and acrylic acid-based copolymers, and the curing agent includes at least one selected from the group consisting of diethyltoluenediamine (DETDA), 3,5-dimethylthio-2,6-diaminotoluene (DMTDA), bis(4-aminobenzoic acid)-1,3-propylidene ester (PDPAB), N,N′-bis(sec-butylamino)diphenylmethane, 2,6-bis(methylthio)-4-methyl-1,3-phenylenediamine, 4-aminobenzoic acid-4-(4-aminobenzoyl)oxyphenyl ester, 4-aminobenzoic acid-4-(4-aminobenzoyl)oxybutyl ester, 4-aminobenzoic acid-4-[4-(4-aminobenzoyl)oxy-3-methylbutyloxy]butyl ester, and bis(methylaminobenzoic acid) methylene ester (MBNA).
[0132] The polishing pad composition can be prepared by sequentially or simultaneously mixing a urethane-based prepolymer, a blowing agent, and a curing agent.
[0133] As an example, the step of preparing the polishing pad composition may be performed by mixing a urethane-based prepolymer with a curing agent and then further mixing with a blowing agent, or by mixing a urethane-based prepolymer with a blowing agent and then further mixing with a curing agent.
[0134] As another example, the urethane-based prepolymer, curing agent, and blowing agent can be put into the mixing process substantially at the same time. If blowing agent, surfactant, and inert gas are further added, they can be put into the mixing process substantially at the same time.
[0135] As another example, the urethane-based prepolymer, blowing agent, and surfactant may be premixed, and the curing agent, or the curing agent with an inert gas, may be added later.
[0136] The mixing initiates the reaction of the urethane-based prepolymer and the curing agent, and allows the blowing agent and the inert gas to be uniformly dispersed in the raw material. In this case, the reaction rate controller may intervene in the reaction at the beginning of the reaction of the urethane-based prepolymer and the curing agent, thereby controlling the reaction rate. Specifically, the mixing may be performed at a speed of 1,000 rpm to 10,000 rpm or 4,000 rpm to 7,000 rpm. Within the above speed range, it may be more conducive to the uniform dispersion of the inert gas and the blowing agent in the raw material.
[0137] In addition, the step of preparing the polishing pad composition may be performed at 50° C. to 150° C. If necessary, it may be performed under vacuum degassing conditions.
[0138] If the blowing agent includes a solid-phase blowing agent, the step of preparing the polishing pad composition may include mixing a urethane-based prepolymer and a solid-phase blowing agent to prepare a first pre-composition; and mixing the first pre-composition and a curing agent to prepare a second pre-composition.
[0139] The first pre-composition may have a viscosity at about 80° C. of about 1,000 cps to about 2,000 cps, about 1,000 cps to about 1,800 cps, about 1,000 cps to about 1,600 cps, or about 1,000 cps to about 1,500 cps.
[0140] If the foaming agent includes a gas-phase foaming agent, the step of preparing the polishing pad composition may include preparing a third pre-composition including a urethane-based prepolymer and a curing agent; and adding the gas-phase foaming agent to the third pre-composition to prepare a fourth pre-composition. In one embodiment, the third pre-composition may further include a solid-phase foaming agent.
[0141] According to one embodiment, the step of preparing the polishing layer includes preparing a mold preheated to a first temperature; injecting the polishing pad composition into the preheated mold and curing it; and post-curing the cured polishing pad composition at a second temperature higher than the preheated temperature.
[0142] In one embodiment, the temperature difference between the first temperature and the second temperature may be about 10° C. to about 40° C., for example, about 10° C. to about 35° C. or about 15° C. to about 35° C. As a specific example, the first temperature may be about 60° C. to about 100° C., about 65° C. to about 95° C. or about 70° C. to about 90° C. As a specific example, the second temperature may be about 100° C. to about 130° C., for example, about 100° C. to about 125° C. or about 100° C. to about 120° C.
[0143] Curing the polishing pad composition at the first temperature can be performed for about 5 minutes to about 60 minutes, about 5 minutes to about 40 minutes, about 5 minutes to about 30 minutes, or about 5 minutes to about 25 minutes.
[0144] The step of post-curing the polishing pad composition cured at the first temperature at the second temperature can be performed for about 5 hours to about 30 hours, about 5 hours to about 25 hours, about 10 hours to about 30 hours, about 10 hours to about 25 hours, about 12 hours to about 24 hours, or about 15 hours to about 24 hours.
[0145] Subsequently, the step of injecting the polishing pad composition into the mold and curing it may be performed at a temperature of 60° C. to 120° C. and at a temperature of 50 kg / m 2 Up to 200kg / m 2 under pressure conditions.
[0146] In addition, the above preparation method may further include the steps of cutting the surface of the polishing pad obtained, machining grooves on the surface, bonding it to a lower part, inspecting, and packaging. These steps may be performed according to a conventional method for preparing a polishing pad.
[0147] As an embodiment, the method for preparing a polishing pad may further include processing at least one side of the polishing layer. The step of processing at least one side of the polishing layer may include forming a groove on at least one side of the polishing layer; performing wire turning on at least one side of the polishing layer; and performing roughening on at least one side of the polishing layer.
[0148] The grooves may include at least one of concentric circular grooves spaced at a certain interval from the center of the polishing layer; and radial grooves continuously connected from the center of the polishing layer to the edge of the polishing layer. Wire turning may be performed by cutting the polishing layer to a certain thickness using a cutting tool. Roughening may be performed by machining the surface of the polishing layer using a grinding wheel.
[0149] Method for manufacturing semiconductor device
[0150] According to another embodiment, a method of manufacturing a semiconductor device includes polishing a surface of a semiconductor substrate using the polishing pad.
[0151] Specifically, a method for preparing a semiconductor device may include providing a polishing pad according to one embodiment; and relatively rotating a polishing surface of the polishing layer and a surface of the semiconductor substrate while a surface of the polishing layer of the polishing pad contacts a surface of the semiconductor substrate to polish the surface of the semiconductor substrate.
[0152] Figure 2 A method for manufacturing a semiconductor device using a polishing pad according to an embodiment is shown. Figure 2When the polishing pad (100) according to one embodiment is fixed on the polishing plate (200), a semiconductor substrate (600) as an object to be polished is placed on the polishing pad (100). In this case, the surface of the semiconductor substrate (600) to be polished is in direct contact with the polishing surface of the polishing pad (100). The polishing slurry (400) can be sprayed onto the polishing pad through a nozzle for polishing. The flow rate of the polishing slurry (400) supplied through the nozzle can be about 10 cm / s or less depending on the purpose. 3 / min to about 1,000cm 3 / min. For example, it can be about 50cm 3 / min to about 500cm 3 / min, but not limited to this.
[0153] Thereafter, the semiconductor substrate (600) and the polishing pad (100) rotate relative to each other, thereby polishing the surface of the semiconductor substrate (600). In this case, the rotation direction of the semiconductor substrate (600) and the rotation direction of the polishing pad (100) may be the same direction or opposite directions. The rotation speed of the semiconductor substrate (600) and the polishing pad (100) may be selected in the range of about 10 rpm to about 500 rpm according to the purpose. For example, it may be about 30 rpm to about 200 rpm, but is not limited thereto.
[0154] The semiconductor substrate (600) mounted on the polishing head (510) is pressed against the polishing surface of the polishing pad (100) with a predetermined load to contact therewith, and then its surface can be polished. The load applied by the polishing head (510) to the polishing surface of the polishing pad (100) through the surface of the semiconductor substrate (600) can be between about 1 gf / cm and about 2 gf / cm according to the purpose. 2 To about 1,000gf / cm 2 For example, it can be about 10 gf / cm 2 To about 800gf / cm 2 , but not limited to this.
[0155] In one embodiment, the semiconductor substrate (600) as the object to be polished may include an oxide layer, a tungsten layer, or a composite layer thereof. Specifically, the semiconductor substrate (600) may include an oxide layer, a tungsten layer, or a composite layer of an oxide layer and a tungsten layer. The composite layer of the oxide layer and the tungsten layer may be a multilayer film in which the tungsten layer is stacked on one side of the oxide layer; or may be a single-layer film in which an oxide region and a tungsten region are mixed in a single layer. Since the object to be polished has such a film material and the polishing pad has the characteristics according to the embodiment, the semiconductor device manufactured according to the method for manufacturing a semiconductor device may have minimal defects.
[0156] In one embodiment, the method for preparing a semiconductor device may further include, in the step of polishing the object to be polished, supplying any one of a slurry for polishing an oxide layer and a slurry for polishing a tungsten layer; or sequentially supplying a slurry for polishing an oxide layer and a slurry for polishing a tungsten layer to the polishing surface.
[0157] For example, if the semiconductor substrate as the object to be polished includes an oxide layer, the method for preparing a semiconductor device may include supplying a slurry for polishing the oxide layer. If the semiconductor substrate includes a tungsten layer, the method for preparing a semiconductor device may include supplying a slurry for polishing the tungsten layer. If the semiconductor substrate includes a composite layer of an oxide layer and a tungsten layer, the method for preparing a semiconductor device may include sequentially supplying a slurry for polishing the oxide layer and a slurry for polishing the tungsten layer to the polishing surface. Here, depending on the method, the slurry for polishing the oxide layer may be supplied first, and then the slurry for polishing the tungsten layer; or the slurry for polishing the tungsten layer may be supplied first, and then the slurry for polishing the oxide layer may be supplied.
[0158] In one embodiment, in order to keep the polishing surface of the polishing pad (100) in a state suitable for polishing, the method for preparing a semiconductor device may further include processing the polishing surface of the polishing pad (100) using a dresser (470) while polishing the semiconductor substrate (600).
[0159] Since the polishing pad according to one embodiment has a chlorine content in the polishing layer adjusted to a certain range, the size of debris can be reduced while maintaining the excellent physical properties and performance of the polishing pad, thereby minimizing the occurrence of defects and scratches in the CMP process. Therefore, the polishing pad can be used to efficiently prepare high-quality semiconductor devices.
[0160] Example
[0161] The present invention will be described in detail below by way of examples. The following examples are intended to further illustrate the present invention, and the scope of the examples is not limited thereto.
[0162] Polishing pad preparation
[0163] Example 1
[0164] (1) Preparation of urethane-based prepolymer
[0165] Toluene diisocyanate (TDI), dicyclohexylmethane diisocyanate (H12MDI), polytetramethylene ether glycol (PTMEG), and diethylene glycol (DEG) were added to a four-necked flask and then reacted at 80°C for 3 hours to prepare a urethane-based prepolymer having 10 wt% of NCO terminal groups (NCO%<1).
[0166] (2) Preparation of polishing pad
[0167] A casting machine is provided with a storage tank and a feed pipe containing raw materials such as urethane-based prepolymer, curing agent, inert gas, and foaming agent. The above-prepared urethane-based prepolymer, curing agent (4,4′-methylenebis(2-chloroaniline), MOCA), solid-phase foaming agent (acrylonitrile / ethylene dichloride, expansion foam type, average particle size: 40 μm to 42 μm), inert gas (N2), and silicon-based surfactant (manufacturer: Evonik) are respectively charged into the storage tank. Here, the feeding amount of the solid-phase foaming agent is 1.5 parts by weight relative to 100 parts by weight of the urethane-based prepolymer, and the feeding equivalent ratio of the urethane-based prepolymer and the curing agent is 1:1, and the total feeding amount is 10 kg / min.
[0168] Subsequently, the raw materials were delivered to the mixing head at a constant speed through respective feed pipes while being stirred (mixing head rotation speed was about 5,000 rpm). A mold (1,000 mm × 1,000 mm × 3 mm) was prepared and preheated at a temperature of 80°C. The stirred mixture was injected into the mold and reacted to obtain a solid cake-shaped molded article. Subsequently, the top and bottom of the molded article were each ground flat to obtain a polishing layer for a top pad.
[0169] Subsequently, the polishing layer was subjected to surface milling and groove forming steps and laminated with a support layer for a base pad by hot melt adhesive to prepare a polishing pad. In this case, a double-sided tape (model: 442JS, manufacturer: 3M) was laminated under the support layer so that it could be attached to the polishing disk of the CMP equipment.
[0170] Example 2
[0171] A polishing pad was prepared in the same manner as in Example 1, except that a solid-phase foaming agent (acrylonitrile / methacrylonitrile copolymer, expanded type, average particle size: 40 μm to 42 μm) was used in step (2).
[0172] Example 3
[0173] A polishing pad was prepared in the same manner as in Example 1, except that the equivalent ratio of the urethane-based prepolymer to the curing agent in step (2) was 1:0.8.
[0174] Comparative Example 1
[0175] As Comparative Example 1, a commercially available polishing pad (model name: IK4140, manufacturer: DuPont) was used.
[0176] Comparative Example 2
[0177] As Comparative Example 2, a commercially available polishing pad (model name: IC1010, manufacturer: DuPont) was used.
[0178] Test Example 1: Sound Absorption Coefficient and Damping Ratio
[0179] The sound absorption coefficient and the damping ratio of the polishing pads of Examples 1 to 3 and Comparative Examples 1 to 2 were respectively measured according to KS F 2814-2.
[0180] Specifically, according to KS F 2814-2, the polishing pad is cut, the sample is placed in an impedance tube, and a plane wave sound source is generated in the tube to measure the sound pressure. In addition, the maximum sound absorption coefficient is calculated according to the following equation 1. In this case, the operating frequency range is 500Hz to 4,000Hz.
[0181] [Equation 1] Sound absorption coefficient = (I i –I r ) / I i =(I a +I t ) / I i
[0182] In Equation 1, when the polishing pad is cut (diameter: 45 mm) to measure the sound pressure in an impedance tube according to KS F 2814-2, I i is the intensity of the incident sound, I r is the intensity of the reflected sound, I a is the intensity of absorbed sound, and I t is the intensity of transmitted sound.
[0183] Test Example 2: Polishing Rate (Removal Rate)
[0184] The polishing pads of Examples 1 to 3 and Comparative Examples 1 to 2 were respectively fixed on the polishing plate of the CMP equipment, and a silicon wafer (300 mm in diameter) was set with the silicon oxide layer facing downward. Then, a CMP process was performed to measure the polishing rate.
[0185] Specifically, the silicon oxide layer is polished under a polishing load of 4.0 psi, while the polishing disk is rotated at a speed of 150 rpm for 60 seconds, and the calcined cerium oxide slurry or calcined silicon dioxide slurry is supplied to the polishing pad at a rate of 250 ml / min. After polishing, the silicon wafer is removed from the carrier, mounted in a centrifugal dryer, cleaned with deionized water, and then dried with nitrogen for 15 seconds. On the dried silicon wafer, a thickness measuring instrument of a spectroscopic reflectometer type (model: SI-F80R, manufacturer: Keyence) is used to measure the thickness difference of the silicon oxide layer before and after polishing. The polishing rate is calculated according to the following mathematical equation 1.
[0186]
Mathematical equation 1
[0187] Test Example 3: Defect variation measurement
[0188] The defect changes of the polishing pads of Examples 1 to 3 and Comparative Examples 1 and 2 before and after polishing were measured, respectively.
[0189] Specifically, polishing was performed using a CMP polisher in the same manner as in Experimental Example 2. After polishing, the silicon wafer was transferred to a cleaning device and cleaned with 1% HF, deionized water (DIW), and 1% H2NO3 for 10 seconds, respectively. Subsequently, it was transferred to a centrifugal dryer, cleaned with deionized water (DIW), and then blown dry with nitrogen for 15 seconds. A defect measurement device (manufacturer: Tenkor, model: XP+) was used to measure the defect changes of the dried silicon wafer before and after polishing. Specifically, the total number of scratches, vibration marks, pits, and residues on the wafer surface was measured.
[0190]
Table 1
[0191]
[0192] As can be seen from Table 1 above, the polishing pads of Examples 1 to 3 have excellent sound absorption characteristics, significantly reduced defects and scratches, and excellent polishing rates. Specifically, the polishing pads of Examples 1 to 3 have a maximum sound absorption coefficient of 0.1 or more in the frequency range of 500 Hz to 4,000 Hz, indicating that their sound absorption characteristics are very excellent compared to the conventional polishing pads of Comparative Examples 1 and 2 (see Table 1). Figure 1 ). In addition, the polishing pads of Examples 1 to 3 have a maximum sound absorption coefficient of more than 0.1 in the frequency range of 500 Hz to 4,000 Hz; therefore, it is possible to minimize energy loss due to thermal energy or vibration energy during the CMP polishing process, thereby achieving excellent polishing rates compared to Comparative Examples 1 and 2. They also have significantly fewer defects and scratches.
Claims
1. A polishing pad comprising a polishing layer, wherein the polishing layer comprises a urethane-based prepolymer, a foaming agent, and a curing agent, and has a maximum sound absorption coefficient of 0.1 or more measured at a frequency of 500 Hz to 4,000 Hz according to the following equation 1: [Equation 1] Sound absorption system number = (I i –I r ) / I i = (I a +I t ) / I i In Equation 1, when the polishing pad is cut (diameter: 45 mm) to measure the sound pressure in an impedance tube according to KS F 2814-2, I i is the intensity of the incident sound, I r is the intensity of the reflected sound, I a is the intensity of absorbed sound, and I t is the intensity of transmitted sound.
2. The polishing pad according to claim 1, wherein The maximum sound absorption coefficient measured at a frequency of 1,000 Hz to 1,500 Hz is 0.05 or more, and the maximum sound absorption coefficient measured at a frequency of 1,500 Hz to 3,000 Hz is 0.1 or more.
3. The polishing pad according to claim 1, wherein The foaming agent includes a solid-phase foaming agent, and the solid-phase foaming agent includes at least one selected from the group consisting of an acrylonitrile-based copolymer, a methyl methacrylate-based copolymer, a methacrylonitrile-based copolymer, and an acrylic acid-based copolymer.
4. The polishing pad according to claim 3, wherein: The solid phase foaming agent has an average particle size of 5 μm to 100 μm, and is contained in an amount of 0.1 to 5 parts by weight relative to 100 parts by weight of the urethane-based prepolymer.
5. The polishing pad according to claim 1, wherein The curing agent includes at least one selected from the group consisting of 4,4′-methylenebis(2-chloroaniline) (MOCA), diethyltoluenediamine (DETDA), 3,5-dimethylthio-2,6-diaminotoluene (DMTDA), 1,3-propylidene bis(4-aminobenzoate) (PDPAB), N,N′-bis(sec-butylamino)diphenylmethane, 2,6-bis(methylthio)-4-methyl-1,3-phenylenediamine, 4-aminobenzoic acid-4-(4-aminobenzoyl)oxyphenyl ester, 4-aminobenzoic acid-4-(4-aminobenzoyl)oxybutyl ester, 4-aminobenzoic acid-4-[4-(4-aminobenzoyl)oxy-3-methylbutyloxy]butyl ester, and bis(methylaminobenzoic acid) methylene ester (MBNA).
6. The polishing pad according to claim 1, wherein The curing agent may be included in an amount of 5 to 50 parts by weight relative to 100 parts by weight of the urethane-based prepolymer.
7. The polishing pad according to claim 1, wherein: The equivalent ratio of the urethane-based prepolymer to the curing agent is 1:0.5 to 2.
8. The polishing pad according to claim 1, wherein: The polishing layer has a hardness of 50 to 65 Shore D, a tensile strength of 15 to 25 N / mm2, and an elongation of 90 to 130%.
9. The polishing pad according to claim 1, wherein: When the polishing pad is used to polish the silicon oxide layer of a silicon wafer with a ceria slurry, the polishing rate according to the following mathematical equation 1 is: to When the polishing pad is used to polish the silicon oxide layer of a silicon wafer with silicon dioxide slurry, the average polishing rate according to the following mathematical equation 1 is to 【Mathematical equation 1】 10. A method for manufacturing a semiconductor device, comprising polishing a surface of a semiconductor substrate using the polishing pad according to claim 1.